Permeation characteristics of hypericin across Caco‐2 monolayers in the presence of single flavonoids, defined flavonoid mixtures or Hypericum extract matrix. (12th March 2017) - Verjee, Sheela; Kelber, Olaf; Kolb, Christiane; Abdel‐Aziz, Heba; Butterweck, Veronika
Abstract: Objectives: The major aim of this study was to get a detailed understanding of the exposure and fate of hypericin in the Caco‐2 cell system when combined with various flavonoids, mixtures of flavonoids or Hypericum perforatum extract matrix (STW3‐VI). Methods: The permeation characteristics of hypericin in the absence or presence of quercetin, quercitrin, isoquercitrin, hyperoside and rutin were tested. Hypericin (5 μm ) was mixed with single flavonoids (20 μm ) or with different flavonoid combinations (each flavonoid 4 or 10 μm, total flavonoid concentration: 20 μm ). Further, the uptake of hypericin (5 μm ) in the presence of H. perforatum extract matrix (7.25, 29 and 58 μg/ml) was studied. Key findings: Following application of hypericin to the apical side of the monolayer, only negligible amounts of the compound were found in the basolateral compartment. From all tested flavonoids, only quercitrin increased the basolateral amount of hypericin. Dual flavonoid combinations were not superior compared to the single combinations. The amount of hypericin in the basolateral compartment increased concentration‐dependently in the presence of extract matrix (from 0 to 7.5%). Conclusion: Comparing the effects of various flavonoid mixtures vs the extract matrix, it can be concluded that, besides flavonoids, the extract seems to contain further compounds (e.g. phenolic acids or proanthocyanidins) which substantially improve the permeation characteristics of hypericin.